407 Implementation of an Integrated Farm Management Plan to Enhance Reproductive Performance in Beef Cow-Calf Operations. (7th December 2018) - Crites, B; Vanzant, E; Bullock, D; Lehmkuhler, J; Burris, R; Anderson, L
Abstract: The University of Kentucky Beef IRM team has developed a project-based educational program (UK IRM Farm Program) designed to instigate long-term adoption of production practices and increase productivity and profitability. Our current objective was to elucidate changes in production for operations (n=14) after one year of program participation. Prior to enrolling in the IRM Farm Program, producers provided historical production records to obtain baseline information. Comprehensive individual management plans were developed and data was collected at breeding, pregnancy diagnosis, calving, and weaning. Operations were categorized as either controlled (90 ), extended (120 ), or year-round (365 ; n=6, 4, 4, respectively) based upon their prior calving season length. Average herd size was 92, 54, and 22 cows for the 90, 120, and 365 groups, respectively. The calving and weaning percentages increased in four of the six farms in the 90 group. Productivity (kg calf weaned per cow exposed) increased by 34 kg in half of the 90 group operations. In the 120 group, calving season length decreased 5 d, calving percentage decreased 1.2%, but the weaning percentage increased 4.5%. Since there were more and older calves weaned in this group, an average increase of 26 kg of calf weaned per cow exposed was observed. For those in the 365 group, calving season length was reduced by 110 days, calving percentage increased 3.7%, weaning percentage increased 3.2%, and kg of calf weaned per cow exposed increased 15 kg. Across all groups, productivity increased by 11 kg of calf weaned per cow exposed on average. Assuming a price of 162/45 kg, revenue increased 41 per cow exposed or 2, 476 per producer. From these data we conclude that an integrated methodology combined with hands-on training could be an effective pedagogy for increasing adoption of production practices and enhancing productivity and profitability in beef cow-calf operations.